Alcohol consumption patterns among adolescents are related to family structure and exposure to drunkenness within the family: results from the SEYLE project - Rüütel, Erik; Brunner, Romuald; Kaess, Michael (International journal of environmental research and public health, 2014)
There is expedient evidence showing that differences in adolescent alcohol consumption and other risk-behaviour depend on both family structure and family member drunkenness exposure. Data were obtained among adolescents (N = 12,115, mean age 14.9 ± 0.89) in Austria, Estonia, France, Germany, Hungary, Ireland, Israel, Italy, Romania, Slovenia and Spain within the European Union’s 7th Framework Programme funded project, ‘Saving and Empowering Young Lives in Europe (SEYLE)’. The current study reveals how adolescents’ alcohol consumption patterns are related to their family structure and having seen their family member drunk. The results revealed statistically significant differences in adolescent alcohol consumption depending on whether the adolescent lives in a family with both birth parents, in a single-parent family or in a family with one birth parent and one step-parent. The study also revealed that the abstaining from alcohol percentage among adolescents was greater in families with both birth parents compared to other family types. The study also showed that the more often adolescents see their family member drunk the more they drink themselves. There is no difference in adolescent drinking patterns whether they see their family member drunk once a month or once a week. This study gives an insight on which subgroups of adolescents are at heightened risk of alcohol abuse and that decrease of family member drunkenness may have positive effects on the drinking habits of their children.
Gesehen am 05.11.2020